PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT BERBANTUAN PRAKTIKUM TERHADAP HASIL BELAJAR SISWA - Yuliarita, Yuliarita; Muharini, Rini; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the differences in learning outcomes of students who use the cooperative learning model Numbered Head Together (NHT) assisted by practicum with students who use conventional learning models on the material of salt hydrolysis class XI SMA Bina Utama Pontianak and determine the influence of type cooperative learning model NHT assisted by practicum towards student learning outcomes in salt hydrolysis material class XI SMA Bina Utama Pontianak. The form of the research used was quasi experiment with the design of Nonequivalent Control Group Design. The sampling technique in this study was a saturated sample consisting of two classes namely class XI IPA 1 as the experimental class and XI IPA 2 as the control class. Data collection technique in this study was measurement technique. The data collection tool used was a test of learning outcome. The results showed that the learning outcomes of the experimental class with the control class with the sig. value 0,000 <0,05 meant that there were differences in learning outcomes between those using conventional learning and those using NHT cooperative learning models with practical assistance. The NHT type of cooperative learning model with practicum assistance gave an effect of 45.99% on student learning outcomes in class XI salt hydrolysis material SMA Bina Utama Pontianak. Keywords:   Learning Outcomes, NHT, Practicum, Salt Hydrolysis